A Biobjective Approach to Assigning Recreational Activities to Medical Tourists - Paç, Ahmed Burak (Prof.Dr. İskender AKKURT, 2023)
Medical tourism is a growing market due to cost savings for patients and access to treatments unavailable in their home country. Countries offering high-quality medical services at affordable prices have great opportunities for growing their revenue and shares in this market. To increase the welfare of tourists and revenues associated with healthcare tourism, this study proposes a mathematical model for planning the integration of recreational activities to the medical schedules of healthcare tourists. The model achieves this by providing access for medical tourists into appropriate recreational activities based on their medical conditions, availability schedules, and budgets. The proposed integer programming model maximizes a weighted sum of total tourist satisfaction points and profits generated from assigning tourists to recreational activities. It incorporates medical restrictions, ensuring that medical tourists are directed to activities suitable for their medical conditions. The Pareto-efficient frontier for patient satisfaction and company profit is determined utilizing the integer programming model. The proposed model aims for a higher quality experience for medical tourists, optimizing their access to recreational activities while promoting economic growth in the health tourism sector. Computational tests demonstrate that the proposed model efficiently solves instance sizes that may arise in practical contexts and enables iterative solutions for obtaining Pareto-efficient frontiers. © 2024 Elsevier B.V., All rights reserved.
Keywords: Combinatorial optimization; Integer programming; Medical tourism